DYNASTIC POLITICS OF THE DEMOCRATIC ERA IN INDONESIA (HADITH PERSPECTIVE ON NEPOTISM IN POLITICS) - Nurma Yunita; Alfauzan Amin; Toha Andiko; Puspita, Tia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Dynastic politics is a phenomenon where political power is inherited within a single family, often resulting in a concentration of power and a disregard for democratic principles, leading to inequality in the distribution of power. This article discusses the influence of a political system dominated by dynasties in the context of modern governance, particularly its impact on public policy and the limitations of social mobility. In the history of Indonesian governance, dynastic politics has occurred in a hereditary manner, with dynastic political strategies being used as tools to secure power by placing family members or relatives in both formal (government) and informal (projects or businesses) positions. As a result, dynastic politics will continue to evolve, generating both support and opposition amid the implementation of a democracy-based government. There is a discussion of hadith regarding the prohibition of granting positions or providing references based on familial relationships, which contradicts the principles of justice and meritocracy. Therefore, this article explores potential solutions that may support policies of transparency, accountability, and equal opportunities for all individuals, aiming to provide an understanding of the impact of dynastic politics and the importance of an inclusive and fair political system.